A Possible Cause of Nasolacrimal Duct Obstruction: Narrow Angle Between Inferior Turbinate and Upper Part of the Medial Wall of the Maxillary Sinus - Gül, A.; Aslan, K.; Karlí, R.; Aritürk, N.; Can, E. (Taylor and Francis Ltd healthcare.enquiries@informa.com, 2016)
Background: To search the relationships between the primary nasolacrimal duct obstruction and the angle between the bony inferior turbinate and upper part of the medial wall of the maxillary sinus. Design: Retrospective study. Participants and methods: Computed tomography findings of 35 patients with primary nasolacrimal duct obstruction and 100 sides of 50 individuals were reviewed. While the study group was composed of patients who had external dacryocystorhinostomy surgery, the control group was composed of patients who had CT scans due to headache, sinusitis and smell dysfunction. Epiphora complaint was evaluated with the lacrimal syringing. The exclusion criteria were: age less than 20 years, previous nose, sinus, turbinate or lacrimal surgery, prior history of maxillofacial fracture, nasopharyngeal malignancy, reflex hypersecretion, and associated pathology of the lacrimal canaliculi. Main outcome measures: The angle of inferior turbinate. Results: The mean angles were 53.2° (range, 37.9–82.9°) for affected side of the study group, 58.6° (range, 32–85.3°) for the unaffected side of the study group and 56.8° (range, 41.2–76.9°) in the control group. The difference between the angles was statistically significant between the study and the control groups (p < 0.05). The difference between the operated and non-operated sides of the study group was also statistically significant (p < 0.05). Conclusion: Although this study was performed in a small group, we thought that the narrow angle between the bony inferior turbinate and upper part of the medial wall of the maxillary sinus might be a possible causative factor in primary acquired nasolacrimal duct obstructions. © 2016 Taylor & Francis Group, LLC.
Keywords: Angle; Computed Tomography; Inferior Turbinate; Maxillary Sinus; Nasolacrimal Duct Obstruction